Farmers' Perspective on Converting Their Paddy Fields in West Java Province - Asmadi Adnan; Septina Marryanti Prihatin (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2023)
The conversion of paddy fields continues to increase rapidly, potentially affecting rice production and threatening national food/rice security. This paper presents farmers' perspectives on various indicators of drivers, controllers and decision-making influencing land conversion. The study is based on a policy and literature approach, supported by field studies using qualitative-quantitative mixed methods in West Java Province. The results show that the driving indicators of land conversion are near main roads/highways; near settlements/trade/industry/ services; and densely populated. Indicators of restraining conversion are space utilization in line with the Spatial Plan; provision of incentives for means of production; and the imposition of land tax disincentives. The most decisive indicators of conversion decision making for farmers' choices are the control / ownership of narrow rice fields; and the production value of rice fields is low.